Determinants of Housing Market Fluctuations: Case Study of Lithuania. (2017) - Tupenaite, Laura; Kanapeckiene, Loreta; Naimaviciene, Jurga
Abstract: The article aims to distinguish the most important determinants of housing market fluctuations in Lithuania for period of 2005–2015. Analysis of housing market cycle performed, major prices' movements and affecting factors discussed. Moreover, in order to distinguish the most significant determinants of housing market fluctuations, expert survey performed and significances of determinants by using the Analytic Hierarchy Process (AHP) method identified. Research reveals that prices movements in Lithuania's housing sector can be largely explained by economic fundamentals as well as housing market indicators.